Stent-within-a-Stent Technique for the Treatment of Dissecting Vertebral Artery Aneurysms - Mehta, Bharat (AJNR Am J Neuroradiol, 2003)
Summary: Subarachnoid hemorrhage from dissecting vertebral artery aneurysms is a well-known phenomenon. With the advent of navigable intracranial stents, these aneurysms are now amenable to endovascular stent placement. However, immediate aneurysm obliteration is often not accomplished, and current covered stents have poor short-term patency rates. We report a series of three patients with intradural dissecting vertebral artery aneurysms treated with a novel endovascular stent-within-a-stent construct using currently available stent technology.